Symbols in life and art : the Royal Society of Canada symposium in memory of George Whalley - Leith, James A.; Whalley, George, 1915-1983 (Published for the Royal Society of Canada by McGill-Queen's University Press, 1987)
Northrop Frye describes the way symbols operate as media of exchange in literature, drawing examples from English literature in difference periods. Eva Kushner examines the increased freedom on expression possible to Renaissance poets because of the availability of a wider range of symbols. Poet and literary historian Douglas Jones probes the use of the railway as a distinctive symbol of both unity and alienation for English Canadians. Abraham Moles analyses the social impact of "dynamic myths" on social changes which break with established traditions. Bogomila Welsh-Ovcharov discusses the function of symbols in the art of Van Gogh. James Leith examines the role of symbols in revolutionary movements, in particular the adaptation of the ancient symbol of the equilateral triangle. Anthony Storr discusses the vital role of symbols in the search for a sense of unity in life. Wilfred Cantwell-Smith considers various world religions as symbolic efforts to give ultimate meaning to life. In conclusion, Norman Mackenzie reflects on all the essays, drawing on his own command of modern literature and culture.